Design of a Wearable Haptic Vest as a Supportive Tool for Navigation - Dharma, Anak Agung Gede; Oami, Takuma; Obata, Yuhki; Yan, Li; Tomimatsu, Kiyoshi (Human-Computer Interaction. Interaction Modalities and Techniques, 2013)
We propose an alternative way to display haptic feedback in ubiquitous computing. We develop a haptic vest that can display detailed haptic feedbacks by utilizing 5x12 arrays of vibrotactile actuators. We conducted a preliminary user testing on 34 stimuli (with four different directions) to measure the effectiveness of various vibrotactile patterns. We have discovered that each stimulus within a given direction has different properties in terms of their apprehensibility and comfort.